Cytotoxicity Test of Ethyl Acetate Fraction and Ethanol Fraction of Papaya Leaf Extract (Carica papaya. L) Against Hep-2 Laryngeal Cancer Cells - Lora Purnamasari (RADINKA JOURNAL OF HEALTH SCIENCE, 2025)
Papaya leaves as a medicine for fever, malaria, increased appetite, constipation, and anti- cancer. In the previous study using the Brine Shrimp Lethality Test (BSLT) ethanol extract of papaya leaf had an LC50 value of 23.73 mg/ml. This suggests that the papaya leaves are a compound, which uses 70% ethanol extract of papaya leaves and has cytotoxic potential. Research objectives: This research aimed to determine the cytotoxic effect of ethanol and ethyl acetate fraction of 70 % ethanol extract of papaya leaf against Hep-2 cells. Performed in vitro by direct calculation method (viable cell count) so its LC50 is known. Ethanol and ethyl acetate fraction of papaya leaf extract as a test solution was made in 5 concentrations, with concentrations of 20.93; 16.26; 12.64; 9.82, and 7.63 µg/ml. Result: The results obtained LC50 ethanol fraction of 11.2616 μg/ml and the ethyl acetate fraction of LC50 12.4of 882 μg/ml. Conclusion: Based on this it can be concluded that the fraction of ethanol and ethyl acetate extracts of papaya (Carica papaya L.) have cytotoxic properties against Hep-2 cells in a range that goes very, very toxic ie 5-50 µg/ml and has the potential to be developed as an anticancer drug.